Aripiprazole as a mood stabilizer in postpartum depression with premorbid passive-dependent personality structure - Stajić, Mladen; Maksimović, Žana M (Scripta Medica, 2019)
Depression is becoming widespread illness. One of the most risky types of depression is postpartum depression. In presented case of postpartum depression, aggravating factor was patient’s personality structure. With the frequent giving up of previous therapy, frequent mood swings, and the present feeling of helplessness, the very treatment of depressive episode within postpartum depression is difficult. In this case study, the introduction of aripiprazole as a drug with a proven effect on mood swings and tendency to mood stabilization, we have come to an excellent result in the form of complete and long-lasting remission.
Keywords: premorbid personality structure; postpartum depression; aripiprazole